Perencanaan Transformasi Sistem Pendidikan di Libya Pasca Revolusi: Kajian Terhadap Kurikulum dan Tata Kelola Lembaga Pendidikan di Libya - Ritonga, Rahmi Anggina; Shidiq, Alvan Satria; Asmendri, Asmendri; Milyasari, Milyasari (Indo-MathEdu Intellectuals Journal, 2025)
This study analyzes the planning of the transformation of the education system in Libya after the 2011 revolution, focusing on the curriculum and governance of educational institutions at the elementary, junior high, and senior high school levels. This study uses a descriptive qualitative approach and analyzes data from literature sources and informants. Data analysis is conducted qualitatively through the stages of data reduction, data presentation, and drawing conclusions. The analysis results indicate that the curriculum implemented in Libya is not yet relevant to the skills needed in the 21st century, and the governance of education is still weak. This study also provides recommendations including refining the curriculum, improving English language learning in schools, and enhancing the performance of the national independent education authority to design standardized curricula in schools. The study also emphasizes the importance of collaboration between the government, educational institutions, and the community to create an education system in accordance with the goals set by Libya.